Autopercepção de estética dental e fatores associados em idosos de uma cidade do sul do Brasil: um estudo transversal - Sachetti, Diandra Genoveva (2019)
The present study evaluated the self-perception of dental aesthetics and associated factors in elderly people in a city in southern Brazil. A cross-sectional observational home-based study with a probabilistic cluster sample was carried out with 282 elderly people aged 60 years or older living in the city of Veranópolis/RS. Clinical examinations of oral health and a structured questionnaire were applied. Concern about the appearance of the teeth was obtained through a questionnaire validated for the Brazilian population and categorized into: appearance concerns and appearance does not concern. Associations were evaluated using the chi-square or Mann-Whitney tests, through frequency distribution. Uni- and multivariate analyzes were performed, using logistic regression to verify associations. Concern with appearance was observed in 13.5% (n=38) of the elderly. In the final multivariate model, concerns about dental appearance, gender and age remained associated. Elderly females had a 2.775 (95% confidence interval, 95%CI: 1.092-7.052) higher Odds Ratio (OR) for concern about dental appearance when compared to elderly males. Being elderly aged 70 years or older was associated with less concern with dental appearance when compared to elderly individuals aged less than 70 4 years. Elderly aged 70 years or older had 55.4% (p=0.034) lower chances of worrying about dental appearance. However, the use and need for dentures were not associated with this concern.